2020
DOI: 10.1038/s41598-019-56979-7
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping of Kernel Traits and Validation of a Major QTL for Kernel Length-Width Ratio Using SNP and Bulked Segregant Analysis in Wheat

Abstract: One RIL population derived from the cross between Dalibao and BYL8 was used to examine the phenotypes of kernel-related traits in four different environments. Six important kernel traits, kernel length (KL), kernel width (KW), kernel perimeter (Kp), kernel area (KA), kernel length/width ratio (KLW), and thousand-kernel weight (TKW) were evaluated in Yangling, Shaanxi Province, China (2016 and 2017), Nanyang, Henan Province, China (2017) and Suqian, Jiangsu Province, China (2017). A genetic linkage map was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 44 publications
7
41
0
Order By: Relevance
“…Those results are consistent with the significant correlation between them. The traits controlled by clusters might be explained by QTL with pleiotropy or a set of closely linked loci [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those results are consistent with the significant correlation between them. The traits controlled by clusters might be explained by QTL with pleiotropy or a set of closely linked loci [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the kernel weight and shape traits, including kernel diameter and kernel weight, exhibited moderate heritability under OP conditions, whereas high heritability under H and HD conditions was found (Table 1). Xin et al [35] found high heritability of kernel shape traits in four different environments. Traits with high heritability and genetic advances can be selected directly for crop improvement [36].…”
Section: Phenotypic Variation For Kernel Weight and Shape-related Tramentioning
confidence: 97%
“…A threshold P value of 0.001 (−log10(P) ≥ 3.0) was used for QTL detection, P value frequently used for many agronomical important quantitative traits [56][57][58]; suggestive QTL were considered at the sub-threshold 2.5 < −log10(P) < 3.0 when declared at least in one year. A QTL was considered stable when detected at −log10(P) ≥ 3.0 in at least two years [41,[58][59][60]. The phenotypic variation (PVE = R 2 ) and additive effect were estimated for each detected QTL.…”
Section: Statistical Analysis and Qtl Detectionmentioning
confidence: 99%